Postcolonoscopy Colorectal Cancer: An Overview and Future Directions - Saikaly,Elias (2021)
Abstract Over the past decade, there has been a great interest in postcolonoscopy colorectal cancer (PCCRC). Its etiology is complex and multifactorial. Monitoring for PCCRC is even more complex. The strategies to decrease the incidence of PCCRC start by defining the problem, identifying the factors contributing to its development, followed by an attempt to define methods to decrease its incidence.We believe that the quality of the colonoscopy and the endoscopist’s expertise are the key factors in decreasing the incidence of PCCRC.